Consuming urban culture in contemporary Vietnam - Drummond, Lisa B. W. (Lisa Barbara Welch), 1961-; Thomas, Mandy, 1959- (London ; New York : Routledge, 2003)
"Consuming Urban Culture in Contemporary Vietnam sheds new light upon the social and cultural changes presently occurring in Vietnam by exploring the realm of Vietnamese popular culture and urban life in a world that has been increasingly affected by global flows of ideas, capital and products. The book provides insights into the dynamic relationship between the recent economic and political changes in Vietnam and the rapidly transforming aspects of urban experience including street life, music, media, magazines, novels, television, dance, film and leisure activities."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Popular culture -- Vietnam; City and town life -- Vietnam; Vietnam -- Social conditions -- 1975-; Vietnam -- Economic conditions -- 1975-; Vietnam -- Civilization -- Western influences; Ebook